PENGARUH DAUN ALPUKAT TERHADAP HIPERTENSI - Tamsuri, Anas; Windarti, Rofik (Akademi Keperawatan Pamenang, 2012)
Hypertension is a condition which the level of blood pressure is exceed than 140/90 mm Hg, which can be confirmed on different occasions. Hypertension may occur caused by heredity, gender, age, obesity, lack of exercise behavior of smoking, alcohol consumption, salt intake and stress berlabih. Impact of hypertension is that a may cause kidney disease, heart disease and death. The objective of study is to determine the benefits of avocado leaves to hypertension. The research method used was experimental studies with a saturated sampling technique. The a population eight person with hypertension aged 40-60 years who are not currently undergoing treatment at the hamlet village Sumbergambi Sonorejo Grogol Kediri Subdistrict. Data was collected using observation sheets. Data analysis was done by calculating the mean, median, mode and standard deviation manually. From the research results showed that most respondents experienced a decrease from the which the average of blood pressure in pretest was 162,5/98,12 and been 141,2/92,12 after administering of avocado leaves. Median blood pressure decreased from 160/100 been 140/90; and the mode of blood pressure was decreased from 160/100 been 140/90. Â From the description above we can conclude that there is a decrease in blood pressure respondents provided stew avocado leaves two times within a period of seven consecutive days. Means avocado leaf can lower blood pressure in hypertensive patients.Â